Tetraspanin co029 expression as a tumor biomarker for monoclonal antibodies preparation: antigenic assessment in colorectal cancer cells - Coutinho, Lucelia; Corsini, Camila; Assis, Jessica; Pedrosa, Maria Luysa; Jeremias, Wander; Santos, Viviane; Cabral, Monica; Mesquita, Ana Sofia; Viviani, Matheus; Nogueira-Rodrigues, Angelica; Grenfell, Rafaella (Brazilian Journal of Oncology, 2022)
Introduction: The identification of innovative cancer biomarkers is a very relevant ongoing quest. Moreover, their role in cancer diagnosis and clinical management has been radically changed in the last few years with the major emphasis on cancer molecular classification, therapeutic target identification, and therapeutic protocol responsivity. tetraspanins are a family of transmembrane proteins correlated with tumor stage, tumor type and patient outcome affecting cell growth, morphology, invasion, and metastasis.Methods: We expressed the 31kDa transmembrane human tetraspanin co029 antigen in Escherichia coli expression host cells using Gateway® platform. Western blotting and ELISA techniques, together with gene sequencing, confirmed the identity of TSP co029 recombinant protein. Forty clones producing antibodies against TSP co029 were obtained. These antibodies were incubated with human colorectal cancer cells in different conditions. ELISA and immunohistochemistry were also performed.Results: The expressed tetraspanin had an appropriate conformation and antigenic integrity to produce antibodies with affinity to the native TSP co029 biomarker. The affinity of the purified recombinant protein and antibodies were confirmed by western blotting, florescent staining of human colorectal cancer cells in fluorescence and confocal microscopies and by ELISA and immunohistochemistry.Conclusion: Our data showed that the recombinant protein and antibodies produced in this study allowed the confirmation of tetraspanin co029 protein presented on the surface of human colorectal cancer cells.
Keywords: Tetraspanins; Recombinant proteins; Antibodies; Monoclonal; Biomarkers, Tumor